Effect of conservation tillage on soil penetration resistance, bulk density, porosity and yield of rice (Oryza sativa) in rice-based cropping system - Abarajitha, P; Subrahmaniyan, K; Elamathi, S; Manimaran, R; Manikandan, K; Sivasankari, D T; Hariniharishma, V P (Plant Science Today, 2026)
Conservation tillage has gained momentum as a sustainable alternative to conventional puddling in rice-based cropping systems, particularly in heavy-textured soils prone to structural degradation. The experiment was conducted during 2024-2025 at the Tamil Nadu Rice Research Institute, Aduthurai, to evaluate the impact of various conservation tillage methods on soil physical properties-namely, bulk density, porosity, penetration resistance and grain yield of rice (Oryza sativa L.) across three consecutive cropping seasons. Twelve treatment combinations were evaluated, including transplanted rice (TPR), non - puddled transplanted rice (NPTR) and direct - seeded rice (DSR), each under three fertiliser levels (100 %, 75 % and 50 % of the recommended dose of fertilisers - RDF), with and without microbial consortia (MC) containing phosphate - solubilising bacteria, potassium - releasing bacteria, zinc - solubilising bacteria and Azospirillum spp. The study revealed that conservation tillage with MC significantly influenced soil physical properties and rice yield. T6 (NPTR with 100 % RDF + MC) had the lowest bulk density (1.40 Mg m-3) at the end of the third season, whereas T1 (TPR with 100 % RDF) maintained the highest bulk density (1.53 Mg m-3), indicating less structural improvement. Soil porosity improved across all treatments, with T6 achieving the highest porosity (52.1 %), representing a 12.28 % increase over the initial value. The mean soil penetration resistance at harvest under T6 had the lowest (135 kPa) at 0–20, 20–40 and 40–60 cm depth in all three seasons. Grain yield was significantly enhanced in T6 (6028 kg ha-¹), followed by T2 (5932 kg ha-1) and T10 (5922 kg ha-1). Hence, the integration of MC with reduced tillage offers a viable strategy to improve soil physical quality and nutrient efficiency by supporting long-term agricultural sustainability.